Plumbing engineering design handbook. Volume 2, a plumbing engineer's guide to system design and specifications (American Society of Plumbing Engineers, 2014)
This Handbook is designed to provide accurate and authoritative information for the design and specification of plumbing systems. This book has 13 chapters including such topics as Sanitary Drainage Systems, On-Site Wastewater Reuse, Vents and Venting, Storm Drainage Systems, Cold Water Systems, Domestic Water Heating Systems, Fuel Gas Piping Systems, Private On-Site Wastewater Treatment Systems, Private Water Wells, Vacuum Systems, Water Treatment, Conditioning, and Purification, Special Waste Drainage Systems, Rainwater and Stormwater Harvesting, and contains many tables and illustrations. This important reference will benefit engineers, plumbing system designers, architects, plant engineers, inspectors, journeymen, students, contractors, and builders.